Does Integrating Cognitive and Psychological Interventions Enhance Wellbeing After Acquired Brain Injury? Study Protocol for a Phase II Randomized Controlled Trial of the VaLiANT (Valued Living After Neurological Trauma) Group Program - Sathananthan, Nick; Morris, Eric M. J.; Gillanders, David; Knox, Lucy; Dimech-Betancourt, Bleydy; Wright, Bradley J.; das Nair, Roshan; Wong, Dana (Frontiers in Rehabilitation Sciences, 2022)
Background and Objectives: Cognitive and emotional changes affect the majority of individuals with acquired brain injury (ABI) and are associated with poorer outcomes. The evidence for ‘siloed’ rehabilitation approaches targeting cognition and mood separately remains mixed. Valued living (i.e., acting consistently with personal values) is associated with better psychological functioning and participation in work and other productive activities. Rehabilitation interventions that concurrently address cognitive and emotional barriers to valued living may therefore result in improved outcomes. VaLiANT (Valued Living After Neurological Trauma) is an 8-week group intervention developed by our team, which uniquely combines cognitive rehabilitation and psychological therapy to improve wellbeing and meaningful participation (i.e., valued living) following ABI. Method: This protocol describes the design and implementation of a Phase II parallel-group randomised controlled trial with blinded outcome assessors, to evaluate the potential efficacy of VaLiANT and the feasibility of a Phase III trial. Participants are adults with a history of ABI at least three months prior to study entry, who experience cognitive and/or emotional difficulties and associated reduced participation in valued activities. Random allocation to the treatment condition (8-week VaLiANT group program) or a usual care waitlist control condition occurs at a 2:1 treatment:control ratio. The primary outcome is wellbeing, measured by the Warwick-Edinburgh Mental Wellbeing Scale. Secondary outcomes include measures of valued living, mood, cognitive complaints, quality of life, community participation, post-traumatic growth, and self-efficacy. All measures are collected across three time points by blinded assessors (baseline, 8-week follow-up, 16-week follow-up). Trial feasibility will be evaluated against recruitment rates, drop-out rates, intervention acceptability, and treatment fidelity (manual adherence and therapist competence). Discussion: This trial will extend current knowledge on how to improve long-term outcomes following ABI by evaluating an innovative integrated, multi-domain approach to rehabilitation concurrently addressing cognitive and emotional barriers to participation in meaningful life roles. Trial Registration: Australian New Zealand Clinical Trial Registry (ANZCTR; identifier: ACTRN12619001243101).